2018
DOI: 10.1007/s00415-018-8746-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting functional outcomes of posterior circulation acute ischemic stroke in first 36 h of stroke onset

Abstract: Posterior circulation acute ischemic stroke constitutes one-fourth of all ischemic strokes and can be efficiently quantified using the posterior circulation Alberta stroke program early computed tomography score (PC-ASPECTS) through diffusion-weighted imaging. We investigated whether the PC-ASPECTS and National Institutes of Health Stroke Scale (NIHSS) facilitate functional outcome prediction among Chinese patients with posterior circulation acute ischemic stroke. Participants were selected from our prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
4
24
1
Order By: Relevance
“…Patients with symptomatic ICVA total occlusions may have low NIHSS scores, whereas the mRS scores of these patients can be high because of serious vertigo, dysphagia, diplopia, or ataxia, so we did not stratify the patients by NIHSS score. Pc-ASPECTS on DWI is helpful in predicting functional outcome in posterior circulation ischemic stroke ( 18 ), and the low pretreatment median pc-ASPECTS (6, IQR, 5–7) on DWI indicated a poor prognosis for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with symptomatic ICVA total occlusions may have low NIHSS scores, whereas the mRS scores of these patients can be high because of serious vertigo, dysphagia, diplopia, or ataxia, so we did not stratify the patients by NIHSS score. Pc-ASPECTS on DWI is helpful in predicting functional outcome in posterior circulation ischemic stroke ( 18 ), and the low pretreatment median pc-ASPECTS (6, IQR, 5–7) on DWI indicated a poor prognosis for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…National Institutes of Health Stroke Scale at admission is also a factor which has an important influence on the rate of END occurring after thrombolytic therapy. Some researchers suggested that NIHSS at admission in high level might increase the mortality and cause poor functional outcomes of patients receiving thrombolytic therapy (Kim et al, ; Lin, Chen, Hu, & Bai, ; Mazya et al, ). However, our results in this meta‐analysis did not conform to these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, various parameters have been used to assess the prognosis of patients with PCCI, including age, diabetes mellitus, GCS score, FOUR scores, atrial brillation, and ejection fraction [18][19][20].…”
Section: Discussionmentioning
confidence: 99%